H.pylori infekcija bērniem Latvijā: prevalence un riska faktori Rīgā, Latvijā - Senaratne, Dhuragajaweera Maha Vidanalage Dananji (Latvijas Universitāte, 2010)
Helicobacter pylori (H.pylori) is a bacterium that inhabits gastric mucosa. It is believed that H.pylori is a risk of contamination by two-thirds of the world's population. Children bacteria spread up to 10% in all countries, industrialized and developed by more than 80% in developing countries. H.pylori is associated with many diseases, including peptic ulcer disease, gastritis and gastric cancer. However, less than one percent of infected persons will develop gastric cancer. Controversial data on the relationship of these organisms throughout the last decades. Objectives           My main aim was to clarify the prevalence of H.pylori infection in children in 2009-2010, compare the distribution of changes over the period 1999-2000 and to explore its relationship with environmental risk factors for children in Latvian. Materials and methods           The prospective study was carried out from 2009 September to April 2010 on H.pylori infection in children aged 2-7 years, Children's Hospital in Riga and in kindergartens. Parents requested to complete a questionnaire and bring the child stools samples. H.pylori infection was determined by fast faecal antigen test. Data were compared with a study that was conducted in 1999 .. The results were analyzed using Statistica (Statsoft) Programme. Results         Common H.pylori positivity was 11.4% (8 / 70), which was significantly lower than outside, compared to 18% in 2000. Hp positivity was associated with lower parental education levels and lower socioeconomic status. Prior antibiotic use, use imported fruit showed a negative association with H.pylori infection. Among all the dyspeptic symptoms, only to loose stools was associated with H.pylori positivity. Conclusions and Recommendations       2010, the overall prevalence of H.pylori among asymptomatic children was 11.4%, which is lower than in 2000. Lower socioeconomic status and parental education levels are associated with higher H.pylori positivity, this relationship was more pronounced 2010th The annual study, compared with 2000.g.veikto study. Negative relationship between H.pylori infection and the use of imported fruit should be explored further in order to assess the role of imported fruit H.pylori infection in the pathogenesis of other risk factors.

Helicobacter pylori is a bacteria found in the gastrici mucosus. H.pylori is believed that infects approximately two-Thirds of the world's population. The prevalence in children ranges from Under 10% of the over 80%, depending on WHERE dared to live. The Highest Infection Rates 3% to 10% are in Developing Countries and the lowest is 0.5% in industrialized nations, the WHERE Rates Continue to decline. H.pylori is related to number of diseases peptic ulcer disease Including, gastritis and gastrici cancer. However, Lias Than One Percent of chronically infected Individuals Will Develop stomach cancer. Controversial data exist about the association With THIS organism Throughout the past Decade. Objectives My main Objective WAS to find out the prevalence of H.pylori Infection in children in 2009-2010, the prevalence Compare Changes within time period of 1999-2000 and the study of ITS association With the Environmental Risk factor in children in Latvia. Materials and Methods A prospective study conducted by WAS from September 2009 - April 2010 on H.pylori Infection. Samples were Taken stool from children aged 2-7 Years at Children's Hospital in Riga and at 4 Kindergartens in Riga and Riga region. The data were compared to the study in 1999 Held With AMOUNT of 146 children. In all the cases "a Questionnaire WAS given to BE filled by the Parent. Results were analyzed Using the Statistica (Statsoft) program. Results         In the total Patient sample (n = 70) H.pylori positivity WAS 11.4% (8 / 70) Which WAS non-significantly lower compared to 18% in 2000th H.pylori positivity WAS significantly lower Associated With Parental educational level and lower socio-Economic status. Previous Antibiotics use, Intake of Imported fruit showed a Negative Association With H.pylori Infection. Among all the dyspeptic symptoms, only loose stool showed an association With H.pylori positivity. Conclusions and Recommendations       In 2010, the total prevalence of H.pylori among asymptomatic children aged 2-5 WAS 11.4%, Which is a non-significantly lower Than in the 2000th Lower socioeconomic status and educational level Parental WAS Associated With Higher H.pylori positivity, the association of WAS expressed more in 2010 compared to the Study performed in the 2000th A Negative association of H.pylori Infection With Intake of Imported fruit Hubble studied BE Further, it Evaluatie the Role of Imported fruit in the pathogenesis of H.pylori Infection. Association of H.pylori positivity With loose stool in anamnesis possibly point to-the symptoms caused by active Infection.
Prevalence of Helicobacter pylori infection and associated risk factors among children in Riga, Latvia
Keywords: Medicīna